Ultrasonographic analysis of lateral liquids and coronal fricatives: judgment of experienced and non-experienced judges - Lima, Fernanda Leitão De Castro Nunes De; Silva, Cássio Eduardo Esperandino Da; Silva, Lídia Maurício Da; Vassoler, Aline Mara De Oliveira; Fabbron, Eliana Maria Gradim; Berti, Larissa Cristina (ABRAMO Associação Brasileira de Motricidade Orofacial, 2018)
ABSTRACTPurpose: to verify if the accuracy in the judgment of the ultrasound (US) images varies according to the experience of the judges and the sound class - alveolar liquids and coronal fricatives.Methods: ultrasound images related to the production of liquids and fricatives in the intervocalic context of the vowel /a/, produced by 20 typical adults, were judged by 15 experienced judges and 15 non-experienced judges. A previous analysis of the images was performed to establish the typical ultrasound pattern of the liquids and fricatives. The accuracy (% of correctness and errors) of the judgments performed by the judges was considered in the analysis. Factorial ANOVA statistical test was used, considering as factors the sound class and the experience of the judges.Results: the Factorial ANOVA showed a significant effect for the accuracy of the judgment only for the sound class, with no significance for the judges' experience or for the interaction between the experience of judges and the sound class. The liquids had a lower accuracy in the judgment, as compared to the fricatives, confirming their articulatory complexity, since they involve the production of two simultaneous gestures.Conclusion: the accuracy in the judgment of the US images did not vary according to the experience of judges, but it was dependent on the sound class. It should be noted, however, that all judges presented previous knowledge about the processes of speech production which may have favored image interpretation.

RESUMOObjetivo: verificar se a acurácia no julgamento das imagens ultrassonográficas (US) varia em função da experiência dos juízes e da classe sonora - líquidas alveolares e fricativas coronais.Métodos: imagens ultrassonográficas relativas à produção das líquidas e fricativas no contexto intervocálico da vogal /a/, produzidas por 20 adultos típicos, foram julgadas por 15 juízes experientes e 15 inexperientes. Uma análise prévia das imagens foi feita para estabelecer o padrão ultrassonográfico típico das líquidas e fricativas. Considerou-se na análise a acurácia (% de acertos e erros) dos julgamentos feito pelos juízes. Utilizou-se o teste estatístico Anova Fatorial, considerando como fatores a classe sonora e a experiência dos juízes.Resultados: a ANOVA Fatorial mostrou um efeito significante para a acurácia do julgamento apenas para a classe sonora, não havendo significância quanto à experiência dos juízes nem quanto à interação entre experiência dos juízes e classe sonora. As líquidas tiveram uma menor acurácia no julgamento comparando às fricativas, confirmando sua complexidade articulatória, uma vez que envolve a produção de dois gestos simultâneos.Conclusão: a acurácia no julgamento das imagens US não variou em função da experiência dos juízes, mas foi dependente da classe sonora. Destaca-se, no entanto, que todos os juízes apresentavam conhecimento prévio sobre os processos de produção de fala o que pode ter favorecido a interpretação das imagens.
Análise ultrassonográfica das líquidas alveolares e fricativas coronais: julgamento de juízes experientes e não experientes
Keywords: Speech; Phonetic; Ultrasonography; Fala; Fonética; Ultrassonografia